The Use of Writing Peer-Feedback - Mila Hayati, Rida Rosyida (RETAIN, 2021)
Recently, there are many studies conducted about peer-feedback. Most result found that peer-feedback has many benefits for the students or even for the teacher. For example, the study conducted by Herdhono in 2015 and Trisnawati in 2009 found that peer feedback can improve the students writing ability. The results of studies show that it is an effective way to reduce errors and mistakes of the students because it helps students to remember their errors and mistakes and to remember the correct ones since their peers provide the correction. Therefore, the purpose of this research was to verify the advantages of written peer-feedback, it is important to revisit peer-feedback technique as the way to improve the students’ writing ability. If peer-feedback technique is good for students in the learning process, do most of teachers use it for the students? This research used survey research as the research design. The subject for this research was the third graders and five teachers of SMA Negeri 15 Surabaya. The researcher used content validity which means every question on the questionnaire represented every single element related to the research question. Site visit had been conducted to avoid data manipulation. After getting the data, the researcher analyzed the data by describing the information from the questionnaire. The findings have shown that the existence of Peer-Feedback is found to be teacher centered in which the teacher fully guided the students to write Peer-Feedback. The reasons why the teacher decides to use written Peer-Feedback is that actually to the give opportunity for the students opportunity in order to make better the quality of their writing. The students claimed the aspect of punctuation and spelling are the easiest one to give Peer-Feedback on. In otherwise, the aspect of vocabulary did not become their main interest in giving written Peer-Feedback. So that, the teacher was not fully able to let the students do the job by themselves. Keywords: Teacher, Peer-feedback, Writing